Depositional processes within the frontal ice-cored moraine system, Ragnar glacier, Svalbard - Ewertowski, Marek; Kasprzak, Leszek; Szuman, Izabela; Tomczyk, Aleksandra (Quaestiones Geographicae, 2010)
The marginal zone of the Ragnar glacier has been divided into four zones: ice surface, proglacial lake, lateral moraine and frontal moraine complex. Detailed researches were carried out in the last one – frontal moraine complex consisting of three subzones: (1) outer moraine ridge, (2) culmination moraine ridge and (3) inner moraine plateau. The frontal moraine complex of the Ragnar glacier shows large variability of lithofacies and depositional processes. The aim of this study was to reconstruct the intensity and variability of depositional processes from early stage of the frontal ice-cored moraines creation till present situation. Debris flow processes, glaciofluvial and glaciolacustrine sedimentation as well as aeolian activity and down- and backwasting are identified as most important processes. Intensity of these processes has varied through the time. Presently the frontal ice-cored moraine complex of the Ragnar glacier is relatively stable, except few areas affected by the river or streams.